2017
DOI: 10.15517/ijds.v20i1.31353
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Most Appropriate Site for the Cold Test in Molar Teeth

Abstract: A test frequently used to complement endodontic diagnoses is the cold test; however, in the last 20 years, authors have reported incorrect results within pulp sensitivity tests. Specifically, a high frequency of false results in posterior teeth, were found. The aim of this study was to identify the most appropriate site for the cold test in molar teeth with a need for endodontic treatment, calculating predictive values, accuracy and reproducibility. A cross-sectional study was performed, evaluating 390 subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…The incisal edge or occlusal surface are sites that have been analyzed by different studies. Researchers have reported high and low values of sensitivity, specificity, accuracy, positive predictive value and negative predictive value with cold and electric tests [16, 22, 26]. On this study we are not evaluating the incisal edge or occlusal surface, since several authors have reported high frequencies of caries, restoration, enamel loss (abrasion) and exposed dentin on those sites [37, 38].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The incisal edge or occlusal surface are sites that have been analyzed by different studies. Researchers have reported high and low values of sensitivity, specificity, accuracy, positive predictive value and negative predictive value with cold and electric tests [16, 22, 26]. On this study we are not evaluating the incisal edge or occlusal surface, since several authors have reported high frequencies of caries, restoration, enamel loss (abrasion) and exposed dentin on those sites [37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…On this study we are not evaluating the incisal edge or occlusal surface, since several authors have reported high frequencies of caries, restoration, enamel loss (abrasion) and exposed dentin on those sites [37, 38]. All these clinical pathologies are associated with false results when using pulp sensibility tests [7, 22]. Therefore, we decided not to include said sites on this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations